EFEKTIFITAS PEMBERIAN TERAPI PUDING DAUN SALAM UNTUK MENCEGAH KONSTIPASI PADA PENDERITA HIPERTENSI PRIMER DI WILAYAH KERJA PUSKESMAS SAIL PEKANBARU - Silvia Elki Putri; Ari Pristiana Dewi; Sofiana " Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract One of complementary therapies for hypertension is salam leaves boiling water that cause constipation if consumed for long time. Salam leaves pudding is a modification of salam leaves boiled water to minimize the effect of constipation. The aims of this study to determine the effectiveness of salam leaves pudding therapy to prevent constipation in patients with primary hypertension. This study used quasy experiment design with post only non-equivalent approach with control group. The study was conducted in Puskesmas Sail with 32 respondents that was 16 respondents to experimental group and 16 respondents to control group by using purposive sampling technique. In the experimental group was given the salam leaves pudding in the morning and evening for 4 days. Measuring instrument was used a sphygmomanometer and defecation observation form. The analysis used univariate analysis to describe the frequency and distribution of the blood pressure and the elimination pattern of the defecation, while bivariate analysis with fisher's exact test to describe differences defecation elimination pattern. The results showed that the experimental group have 16 respondents (100%) not constipation, in the control group as 6 respondents (37.5%) the risk of constipation and 10 respondents (62.5%) not constipation. Statistical test results used of fisher's exact test with p value 0.018 <(α = 0.05), which means that salam leaves pudding can prevent constipation of primary hypertension patients. These results was suggested to decreasing blood pressure and can be help minimize the effects of constipation in patients with primary hypertension escpecially in community nursing interventions. Keywords: Constipation, hypertension, salam leaves pudding